Instrumental variables estimation with flexible distributions - Christian Hansen; Whitney Newey; James B. McDonald; Whitney Newey (Centre for Microdata Methods and Practice (cemmap), 2007)
Instrumental variables are often associated with low estimator precision. This paper explores efficiency gains which might be achievable using moment conditions which are nonlinear in the disturbances and are based on flexible parametric families for error distributions. We show that these estimators can achieve the semiparametric efficiency bound when the true error distribution is a member of the parametric family. Monte Carlo simulations demonstrate low efficiency loss in the case of normal error distributions and potentially significant efficiency improvements in the case of thick-tailed and/or skewed error distributions.
Keywords: 330; Instrumentalvariablen-Schätzmethode; Schätztheorie; Monte-Carlo-Methode; Statistischer Fehler